Sberbank’s Entrance into Turkish Banking Sector and Reasons of This Decision - Yaman, Kemal (International Journal of Economics and Financial Issues, 2014)
In this paper, recent market access of the biggest bank in Eastern Europe, Sberbank of Russia, to the Turkish banking sector is investigated. The motives of Sberbank’s act are considered. Despite a long history of confrontation, Turkey and Russia have come closer in recent years, especially through stronger cooperation in energy sector, trade and tourism. In the first part of this article, economic and political relations between both countries are examined. In the second part, reasons for purchasing Denizbank are investigated where both banks’ positions in their own countries are questioned. Also, the consequences of Sberbank’s entrance to the Turkish banking sector for both countries’ relations are studied. Finally, it is observed that the access of Sberbank will reinforce the economic and social relationship between two countries and it will be a leader for Russian companies to enter Turkey’s prospective and lucrative sectors. Keywords: Banking sector, bank acquisition, business potentials, Sberbank of Russia and Denizbank JEL Classification: F21; G21; G24; G34